Optimalisasi UMKM Hasil Pertanian Nanas melalui e-Commerce di Era Digitalisasi Dusun Bukit Asam Desa Antibar - Nafisiyanda, Nafisiyanda; Rosnani, Titik; Ananda, Fitri Abhellia; Sari, Vriska Monia; Audina, Riska; Agfar, Defran Sutan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Bukit Asam Hamlet area has great potential in the agricultural sector, especially pineapple. In this hamlet, the community has processed their agricultural products into pineapple dodol which is in demand, especially during holidays. However, UMKM actors here still experience obstacles in marketing their products. In the midst of rapid digitalization, farmers should be able to take advantage of e-commerce as an opportunity to reach a wider market, both nationally and internationally. Unfortunately, the Bukit Asam Hamlet community still does not understand how to utilize this technology. This community service aims to expand the reach and services of UMKM actors with marketing training through e-commerce. The methods used in this article are observation, interview, and documentation methods. The method is carried out directly which we have done and provided marketing training through e-commerce. By utilizing e-commerce, they can market products more effectively, and reach consumers more widely, as well as increase profitability and business sustainability. The results of the study in this article show that the integration of e-commerce in the agricultural sector provides great potential in increasing efficiency and profitability and expanding the reach of target markets in product marketing.